If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -4v) + 5 = 104 (1 * 3 + -4v * 3) + 5 = 104 (3 + -12v) + 5 = 104 Reorder the terms: 3 + 5 + -12v = 104 Combine like terms: 3 + 5 = 8 8 + -12v = 104 Solving 8 + -12v = 104 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -12v = 104 + -8 Combine like terms: 8 + -8 = 0 0 + -12v = 104 + -8 -12v = 104 + -8 Combine like terms: 104 + -8 = 96 -12v = 96 Divide each side by '-12'. v = -8 Simplifying v = -8
| 2t-18=0 | | 24x-6=24x+36 | | 0=7v+26 | | ln(x)+2=0 | | -8=t-2 | | 4(4x-2.2)=2x-8.8 | | 7(1+2a)=-105 | | 22x+13=-18x+13 | | ln(2x+1)ln(9-4x)=0 | | ln(2x-1)ln(9-4x)=0 | | 7(x-7)=-98 | | x+4=x-9 | | 17=-6v-2 | | -6=-8m+8-6 | | -(3m-8)=12-m | | -5n+6n=2 | | 5m-4m=8 | | -2x+8x=-18 | | 9=-12t+3 | | 5y-6=2y-30 | | a+b=21 | | -13=-2y+7 | | -12t-3=9 | | -(3m-8)=13-m | | 6(x-3)+3=2x+4(-3+x) | | 3(4x-6)=2(6x+3) | | (-8x-5)=(-2-7x) | | 2x+[2x-(x-4)]=-[-(5-x)] | | 8x-3(2x-3)=-4(2-x)+3(x-4)-1 | | 6(x-3)=3+6x+3x | | 4x-17=3x-12 | | 9-5(3a+5)= |